2000
DOI: 10.1002/1097-4636(200010)52:1<30::aid-jbm5>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preparation conditions on the microstructure and bioactivity of ?-CaSiO3 ceramics: Formation of hydroxyapatite in simulated body fluid

Abstract: Two different reagents, NaOH and NH(4)OH, were used to precipitate CaSiO(3) precursor powders from ethanol solutions of Ca(NO(3))(2). 4H(2)O and Si(OC(2)H(5))(4). The resultant powders of different Ca/Si ratio and residual Na(2)O content exhibited significant differences in the microtexture of the resulting sintered alpha-CaSiO(3) ceramics. The microtexture of the ceramics from the NaOH system (CS-Na) contained smaller grain sizes and a thicker glassy phase at the grain boundaries than those produced using NH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Synthetic HA material is biocompatible and bioactive and is clinically used as an important bone substitute. 11 Some studies have proved that CS is biocompatible, biodegradable, and bioactive, with the ability to stimulate proliferation and osteogenic differentiation of osteoblasts, [12][13][14][15][16] and CS has been shown to have higher bioactivity than calcium phosphate materials. [17][18][19] Abu Bakar et al 20 prepared 20 volume% (vol%) HA-reinforced PEEK composite (HA/PEEK) with a porosity of 60% and pore size ranging from 300 to 600 mm using a leaching of particulate technique employing a suitable pore-forming agent, and these materials were implanted into the distal metaphyseal femur of pigs to evaluate the biological responses and tissue ingrowth of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic HA material is biocompatible and bioactive and is clinically used as an important bone substitute. 11 Some studies have proved that CS is biocompatible, biodegradable, and bioactive, with the ability to stimulate proliferation and osteogenic differentiation of osteoblasts, [12][13][14][15][16] and CS has been shown to have higher bioactivity than calcium phosphate materials. [17][18][19] Abu Bakar et al 20 prepared 20 volume% (vol%) HA-reinforced PEEK composite (HA/PEEK) with a porosity of 60% and pore size ranging from 300 to 600 mm using a leaching of particulate technique employing a suitable pore-forming agent, and these materials were implanted into the distal metaphyseal femur of pigs to evaluate the biological responses and tissue ingrowth of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si) is one of the most abundant elements on earth, and it is also present in the human blood plasma in the form of orthosilicic acid [Si(OH) 4 ] which is vital for the optimum growth and development of bones and collagen in the living organism [24]. Glasses are rich in SiO 2 which yields the formation of surface Si-OH − groups in the SBF, which on their turn ensure active sites for the formation of HA [25]. Further, porous and nanostructured materials (porous Si, polycrystalline Si and CdSe/SiO x nanostructures), obtained by using well-established nanotechnologies were also utilized in our work, since nanosized objects, as well as porous structures are known to promote bone and tissue ingrowth into open pores and they also allow to be easily biodegraded and bioresorbed [24,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…5,6) Siriphannon et al have found that the rate of HAp formation on pure CS ceramic surface was faster than that on the biocompatible A/W glass ceramics and some other bioactive glass ceramics. 7,8) Thus, CS ceramic is expected to be a good implant material. However, the bending strength and fracture toughness of cortical bone are 50-150 MPa and 2-12 MPaÁm 1=2 , respectively, 9) but the CS ceramic shows poor sintering ability (relative density below 90) and mechanical properties (bending strength lower than 70 MPa), 7,8,[10][11][12] which restrict it from the practical application.…”
Section: Introductionmentioning
confidence: 99%